(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2022)
Mitochondrial disorder speaks about anomalies in the metabolic pathways which are controlled by two genomic systems, mitochondrial and nuclear genome which combine to form a respiratory chain. The nuclear genome inscribes the mostly of the respiratory complex protein components and a wide variety of the mitochondrial DNA (Mitochondria DNA) interpretation systems and replication systems. On the other hand, the mitochondrial genome is encoding about 13 subunits of the respiratory complex and RNA components of the mitochondrial translational machinery. This review demonstrates hereditary diseases of humans caused by mutations in mitochondrial DNA and their prevention.